COMPARISON OF ANGLO SAXON AND CONTINENTAL EUROPEAN LEGAL SYSTEMS - Sabrudin, Wahyu (Proceeding International Seminar of Islamic Studies, 2023)
Every country including Indonesia has a legal system to regulate its government. The legal system in principle regulates the life of a society so that conflicts do not occur. Even though conflicts cannot be avoided, the legal system has a role in resolving these conflicts. The comparison that will be put forward by the author in this study is the difference in the legal system of the problem, namely Indonesia and the Netherlands are countries that adhere to the civil law system, while Australia adheres to the common law system, where the fundamental difference between the two legal systems can be seen in the legal system Civil Law takes a written form which is codified in statutes. Meanwhile, the Common Law legal system refers more to customary law, which tends to be unwritten. Although the main legal source of Civil Law is statutory regulations, jurisprudence also has an important role in applying law to the Civil Law system. In contrast to the Common Law legal system, where the main source of law is jurisprudence (judge made by law/binding force of precedent), where legal issues are resolved by case and the results are reflected in judge decisions (jurisprudence).